2016
DOI: 10.1002/wdev.228
|View full text |Cite
|
Sign up to set email alerts
|

β‐catenin‐driven binary cell fate decisions in animal development

Abstract: The Wnt/β‐catenin pathway plays key roles during animal development. In several species, β‐catenin is used in a reiterative manner to regulate cell fate diversification between daughter cells following division. This binary cell fate specification mechanism has been observed in animals that belong to very diverse phyla: the nematode Caenorhabditis elegans, the annelid Platynereis, and the ascidian Ciona. It may also play a role in the regulation of several stem cell lineages in vertebrates. While the molecular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 74 publications
(206 reference statements)
0
15
1
Order By: Relevance
“…S4E) (Hudson et al, 2016). The mechanism of nβ-catenin-mediated transcriptional repression described in the present and previous (Oda- Ishii et al, 2016) studies is different from other mechanisms described in Caenorhabditis elegans and Drosophila melanogaster (Bertrand, 2016;Blauwkamp et al, 2008;Murgan et al, 2015). Thus, nuclear β-catenin-dependent transcriptional repression appears to be mediated by diverse mechanisms.…”
Section: Discussioncontrasting
confidence: 53%
“…S4E) (Hudson et al, 2016). The mechanism of nβ-catenin-mediated transcriptional repression described in the present and previous (Oda- Ishii et al, 2016) studies is different from other mechanisms described in Caenorhabditis elegans and Drosophila melanogaster (Bertrand, 2016;Blauwkamp et al, 2008;Murgan et al, 2015). Thus, nuclear β-catenin-dependent transcriptional repression appears to be mediated by diverse mechanisms.…”
Section: Discussioncontrasting
confidence: 53%
“…Several pathways have been implicated in the control of these terminal asymmetric divisions. In vertebrates and C. elegans, the Wnt pathway plays a role in the regulation of neuronal progenitor asymmetric divisions (reviewed in Bertrand, 2016;Bielen and Houart, 2014). For example, in the mouse cortex, it has been observed that the Wnt pathway regulates the generation of neurons from neural stem cells (Woodhead et al, 2006;Zhang et al, 2010) and the asymmetry of neural stem cell divisions (Delaunay et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…We have previously shown that the terminal asymmetric divisions of embryonic neuronal progenitors are regulated by a particular Wnt pathway termed the Wnt/β-catenin asymmetry pathway (Bertrand and Hobert, 2009). This pathway regulates several asymmetric divisions during C. elegans embryonic and postembryonic development (Bertrand, 2016;Kaletta et al, 1997;Phillips and Kimble, 2009;Sawa and Korswagen, 2013). Whether Wnt ligands regulate the terminal asymmetric divisions of neuronal progenitors in the embryo remains to be determined.…”
Section: Introductionmentioning
confidence: 99%
“…The results presented here led us to tentatively conclude that DWnt2 affects cell fate determination of testis-relevant myoblasts. Indeed, it has been shown that Wnt signaling specifies cell identity of a subset of somatic muscle founder cells in Drosophila embryogenesis ( Baylies et al, 1995 ) and during many other determinations of the fate of the cell ( Bertrand, 2016 ; Munoz-Descalzo et al, 2015 ). However, an additional later role in the migration of testis myotubes cannot be excluded.…”
Section: Discussionmentioning
confidence: 99%